Magnetic field induced multichannel tunable filter properties of photonic band gap materials. Issue 1 (July 2021) - Aly, Arafa H; Awasthi, Suneet K; Mohamed, Asmaa M; Sabra, Walied; Mobarak, M; Matar, Z.S.; Shalaby, A S
Abstract: we have explored the tunable multichannel characteristics of one-dimensional (1D) plasma photonic structure in presence of static magnetic field applied externally parallel and anti-parallel to the direction of propagation under normal incidence. We have theoretically examined the transmission characteristics of the binary photonic design consisting of alternate layers of CaF2 and magnetic cold plasma layers by means of transfer matrix method (TMM) which is amongst the one of the popular techniques for simulating 1D multilayer periodic structures based on MATLAB. The proposed structure possess N-1 number of distinct transmission peaks, each of unit transmission called as transmission channels in transmission spectra for given the number of periods N > 1. In this study N varies from 2 to 6 in steps of 1 to get 1 to 5 transmission channels respectively. Further we have also investigated how these transmission channels can be repositioned inside PBG by applying the static magnetic field (B) externally under right hand polarization (RHP) and lift hand polarization (LHP) configurations for given N at B = 0T, 0.02T, 0.04T and 0.06T. The reason behind the existence of these transmission channels is due to the superposition of evanescent and propagating waves inside plasma and dielectric layers respectively. The existence of these transmission channels inside PBG is different from the transmission bands which are formed due to the interference of forward and backward propagating waves. Besides this the tuning sense of the transmission channels at fixed B applied parallel or anti parallel to direction of periodicity, by changing the angle of incidence corresponding to TE and TM polarization case has also been examined to get some more useful and interesting tunable multichannel characteristics of the current design which cannot be obtained in conventional PPCs.